Five myths of COVID-19 for the team physician - Mercurio, A. M.; Gianakos, A. L.; Mulcahey, M. K.; Sutton, K. M. (HSS Journal, 2020)
This paper focuses on five myths that may affect a team`s return-to-sport protocols and considerations based on the available data. As COVID-19 cases continue to rise nationwide, including among athletes, return-to-play protocols and contingency plans are becoming even more important. Amid a changing landscape in summer 2020, we present information that may be useful to the team physician at any sporting level in crafting recommendations and educating athletes, coaches, and allied team staff about some common misconceptions and risks.